Transmission of Helicobacter pylori - Mahadeva, Sanjiv; Goh, Khean Lee (Faculty of Medicine, University of Malaya, 2001)
Helicobacter pylori infection is a common world-wide phenomenon that has been show to be responsible for gastritis, between 80-95% of peptic ulcer disease(1), and has been implicated in the pathogenesis of both gastric cancer and mucosa associated lymphoid tissue lymphom a(2). Effective public health interventions to reduce the incidence of infection are dependent on a good understanding of those most at risk of acquisition and of the sources and routes of transmission